FAKTOR YANG MEMPENGARUHI KESADARAN BEDERMA MASYARAKAT BANDA ACEH PADA LEMBAGA AKSI CEPAT TANGGAP - Tasya Nurfadila; Eka Nurlina (FEB Universitas Syiah Kuala, 2022)
This study aims to analyze the effect of social media and brand awareness on the awareness of charity with religiosity as a mediating variable. The data collection instrument used a quesitionnaire with a sample of 100 people in Banda Aceh City. Hipothesis testing using path analysis techniques used are path analysis and the Sobel test. Based on the results of the analysis in this study, it was found that social media had a positive and significant effect on religiosity. Brand awareness had a positive and significant effect on social media. Social media had a positive and significant effect on awareness of charity. Brand awareness had a significant and positive effect on awareness of charity. Religiosity has a positive and significant effect on awareness of charity. The results of the Sobel test on the indirect effect show that social media has no positive and significant effect on awareness of charity with religiosity as a mediating variable. Brand awareness has a positive and significant influence on awareness of charity, with religion as a mediating variable.